2020
DOI: 10.1021/acs.jpcc.0c07090
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Binary Mixtures of Ionic Liquids in ZIF-8 for Selective Gas Storage and Separation: A Perspective from Computational Approaches

Abstract: Carbon dioxide is one of the major causes of global climatic changes. Efficient separation of CO 2 from different gaseous mixtures can be helpful in flue gas separation, gas sweetening, natural gas processing, and so forth. Adsorption in porous materials is emerging as one of the best techniques in this regard. Also CO 2 is easily soluble in ionic liquids (ILs). Hence, we have designed IL (designer solvent)-based composite materials by impregnating ILs into the pores of zeolitic imidazolate framework (ZIF)-8. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…Recently, metal–organic frameworks (MOF NPs) have attracted great attention in selective catalysis, gas storage and separation, and drug delivery owing to their large surface area, high and tunable porosity, and good functionalization . In particular, zeolitic imidazolate framework-8 nanoparticles (ZIF-8 NPs), a subclass of MOF NPs, have been utilized as a smart nanocarrier for accommodating functional nucleic acids containing siRNA, CpG, and DNAzyme by electrostatic interactions. Moreover, the nanoscale ZIF-8 NPs can be delivered into cells via the endocytosis pathway and then decomposed under acidic conditions of endo-lysosomes to motivate the controlled cargo release. Recent studies have found that Cu 2+ -doped ZIF-8 NPs (Cu/ZIF-8 NPs) not only maintain the unique properties of ZIF-8 NPs but also supplement an adequate amount of DNAzyme cofactor to implement the biocatalytic operation of the Cu 2+ -dependent DNAzyme in living cells. , Thus, the Cu/ZIF-8 NP-based nanoplatform could be employed as a versatile self-driven nanocarrier for the efficient delivery of DNAzyme logic circuits into cells.…”
mentioning
confidence: 99%
“…Recently, metal–organic frameworks (MOF NPs) have attracted great attention in selective catalysis, gas storage and separation, and drug delivery owing to their large surface area, high and tunable porosity, and good functionalization . In particular, zeolitic imidazolate framework-8 nanoparticles (ZIF-8 NPs), a subclass of MOF NPs, have been utilized as a smart nanocarrier for accommodating functional nucleic acids containing siRNA, CpG, and DNAzyme by electrostatic interactions. Moreover, the nanoscale ZIF-8 NPs can be delivered into cells via the endocytosis pathway and then decomposed under acidic conditions of endo-lysosomes to motivate the controlled cargo release. Recent studies have found that Cu 2+ -doped ZIF-8 NPs (Cu/ZIF-8 NPs) not only maintain the unique properties of ZIF-8 NPs but also supplement an adequate amount of DNAzyme cofactor to implement the biocatalytic operation of the Cu 2+ -dependent DNAzyme in living cells. , Thus, the Cu/ZIF-8 NP-based nanoplatform could be employed as a versatile self-driven nanocarrier for the efficient delivery of DNAzyme logic circuits into cells.…”
mentioning
confidence: 99%
“…Compared with anions, the cationic part of ILs with a hydrophobic alkyl chain and an imidazolium ring tends to hold stronger interactions with the ZIF-8 framework. 33,34 Intriguingly, defects within ZIF-8 frameworks can enhance their interactions with cations (Fig. 1(e)).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, ZIFs materials containing ILs provided high adsorption capacity. The use of binary ILs enhanced the CO2 selectivity by 3.5-fold compared to simple ILs@ZIF-8 [141] . A binary ILs with both hydrophobic-hydrophobic properties exhibited higher CO2 selectivity.…”
Section: Defectsmentioning
confidence: 99%